Social Support for Digital Inclusion: Towards a Typology of Social Support Patterns - Asmar, Axelle (2020)
This article contributes to a better understanding of patterns of social support in relation to digital inequalities. Based on an extensive qualitative study, the diversity of support networks and supports seeking patterns are unveiled. A typology of six patterns of help-seeking is presented and described: the support-deprived, the community-supported, the supported through substitution, the network-supported, the vicarious learners, and the self-supported. The article also critically engages with the often unnuanced academic literature on social support. The research and the typology reveal that the quality of support, as well as the availability of potential or actual support, is not only influenced by socio-economic factors. Rather, the strength of the relationship and the level of intimacy between individuals is an important predictor of support-seeking. As such, this article shows that mechanisms of in/exclusion are highly social, as they entail a diversity of formal and informal support-seeking patterns, which in turn have an important influence on the adoption and use of digital media. The article argues that understanding such mechanisms is rooted in reconciling micro-level interactions to macro-level patterns of inequalities. To show the specificity of social support within digital inequalities research, and to demarcate the concept from definitions of other academic disciplines, the concept of social support for digital inclusion is introduced. It is defined as the aid (emotional, instrumental, and informational) that an individual receives from his/her network in his/her use of digital technologies.